TRANSLATION OF EXPRESSIVE SPEECH ACTS AND THEIR ACCEPTABILITY LEVEL IN ANIMATED FILM DUBBING OF THE TOY MAKER AND HIS DAUGHTER - Yunita Widiyantari; Ika Oktaria Cahyaningrum (Acceleration: Multidisciplinary Research Journal, 2024)
Dubbing makes the audience understand the storyline of a film more easily.  The moral, cultural, and meaningful messages that the film wants to convey can be expressed and absorbed well by the audience.  The study aims to observe the types of change from expressive speech acts in English to those in Indonesian. Apart from that, another aim is to assess the level of translation quality, especially regarding the acceptability of the translation of expressive speech acts in the animated film The Toy Maker and His Daughter. The data collection method is carried out by watching films and translations, identifying expressive speech act data, classifying them into types of speech, and assessing the quality of the level of acceptance of the meaning of the expressive speech. The research revealed eight types of expressive speech acts in this film, namely praising, thanking, insulting, complaining, congratulating, regretting, pitying, and blaming. The most data was praised namely 14 data. In terms of translation acceptability level, 89.58% of the data obtained a score of three. This means that the translation is considered to feel natural. The terms are commonly used and familiar to Indonesian viewers.